Peran Konten Misteri Dalam Pembentukan Personal Branding Youtuber - Leasfita, Ade; Elysa, Refani (Jurnal Mahardika Adiwidia, 2022)
Youtube is one of society's digital platforms with this digital media era making it easy for anyone to create messages and spread messages, finally the term youtuber also appears. One of the people who can be said to be a youtuber is Andi SS, he is a youtuber with mystery-themed content, conspiracy theories, and discusses news that is viral among the world. This study uses a qualitative research type. Research data were collected through interviews and observations. The theory used in this research is informative. The results of this study indicate that mystery content has a role in the formation of personal branding. Content has a big role in delivering messages, ideas, and ideas, message topics, and in easy-to-understand language. In distributing this content, YouTuber AndinSS utilizes digital media, namely YouTuber